Kendali Motor DC Brushless Modifikasi Mengunakan IC Ne555 Dan CD4017 - Wiwin A Oktaviani; Ibnu Sukri (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2021)
In general, the Brushless DC motor speed controller uses an Atmega 16 microcontroller and a MOSFET, which often increases the MOSFET's temperature, especially when the motor is loaded. This article discusses the use of the IC NE555 and CD4017 as a frequency regulator to the MOSFET gate by periodically igniting the forward voltage from the change in the potentiometer value. We carried out the test in an unloaded and unloaded state with voltage variations of 2.5 Vac, 7.5 Vac, 12.5 Vac, and 19.5 Vac. The test results show an excellent tool response where the higher the frequency value, the motor speed will increase. The maximum speed when unloaded reaches rpm at a frequency of 574.6. Whereas in the load test, the full speed reaches 20987 rpm at a frequency of 524.675 Hz. During the test, there was no temperature increase in the MOSFET.